Analysis of green packaging adoption behavior in culinary small and medium enterprises in Bandar Lampung City: The SOR model approach towards sustainable innovation - Risda Marvinita; Tazkiyah Sakinah; Nuzul Inas Nabila; Azzahra Angelita; Lintang Nur Rohmah (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the behavioral factors influencing the adoption of green packaging among culinary micro, small, and medium enterprises (MSMEs) in Bandar Lampung using the Stimulus–Organism–Response (SOR) framework. As sustainability concerns become increasingly important within the business environment, understanding the determinants of environmentally responsible practices among MSMEs is essential for promoting sustainable entrepreneurship. Employing a quantitative explanatory approach, data were collected from 205 culinary MSME owners through purposive sampling and analyzed using Structural Equation Modeling (SEM) to investigate the relationships among green packaging innovation, perceived environmental value, attitudes toward green innovation, and adoption intention. The findings reveal that green packaging innovation positively influences MSMEs’ perceptions of environmental value and fosters favorable attitudes toward green innovation, which subsequently enhance their intention to adopt environmentally friendly packaging practices. These results support the applicability of the SOR model in explaining behavioral responses to sustainability-oriented innovations within the MSME sector. Nevertheless, the study also identifies several barriers to adoption, including higher production costs, limited access to eco-friendly materials, and relatively low levels of environmental awareness among business owners. The study contributes to the growing literature on sustainable entrepreneurship and green innovation by providing empirical evidence from the culinary MSME sector in an emerging economy. Future research is encouraged to incorporate broader samples and additional behavioral, institutional, or contextual factors to further explain green innovation adoption among small businesses. Keywords: Green Packaging; SOR Model; MSMEs; Sustainable Innovation